LETTER TO EDITOR: Role of Oxygen-Ozone (O2-O3) Injection in Discogenic Pain - Asmita P. Karnalkar; Pratap B. Karnalkar (Journal of Krishna Institute of Medical Sciences University, 2012)
Medical ozone is a mixture of oxygen-ozone (O2-O3) which can be used for several medical applications. Ozone chemonucleolysis by injecting mixture of oxygen-ozone is a minimally invasive technique to treat discogenic pain. Considering invasiveness and possible morbidity with surgery for discogenic pain, minimal invasive techniques are preferred. Ozone chemonucleolysis is currently available such technique which has shown promising result in recent years. It involves injection of ozone gas into the intervertebral disc under fluoroscopic guidance. This article deals with mechanism of action, indications, procedure and side effects of this technique in detail.